Offer Opportunities of Levelling Online Courses for Latvia (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Currently, all European countries, including Latvian, there is a decrease of students' mathematical knowledge. As a result, universities and high schools face the challenge of filling the knowledge in mathematics among students. This has resulted in increasing the level of knowledge disparity in study groups. And experience shows that many students need extra - levelling courses. One of solution of such courses would be a free on-line levelling courses.